Big tech tyrants : how Silicon vValley's stealth practices addict teens, silence speech and steal your privacy - Brown, Floyd, 1961- (Highbridge Audio, 2019)
"Boy Kings," or Big Tech Tyrants, are considered the most powerful individuals in the world. They're the autocratic aristocrats who run the tech giants in Silicon Valley, and these social platform operators have gained a non-elected (or, should we say, a self-elected) authoritarian power. They wield it with more effectiveness and precision than any sitting government or military strategist. Big Tech Tyrants boast riches beyond emperors of old but act like juveniles who don't want to grow up. They are modern-day robber barons. Big Tech Tyrants don't know the meaning of privacy, when it comes to you. They try to make you believe they will give their products away for free as a service to society, when really, they are vacuuming your personal data. They use this data to discover your deepest secrets. Are you or your partner trying to get pregnant' Are you underwater financially' Are you having an extramarital affair' Do you have a tidy nest egg' Are you a Trump supporter' Are you a Bernie Sanders follower' Are you a Scientologist, Mormon, Christian, or Buddhist' Your personal data is extremely valuable to them, and they use it and abuse it. Big Tech Tyrants is an eye-opening book for anyone living in the twenty-first century.